Induction of ApL3 Expression by Trehalose Complements the Starch-Deficient Arabidopsis Mutant adg2-1 Lacking ApL1, the Large Subunit of ADP-Glucose Pyrophosphorylase - Fritzius, Thorsten (American Society of Plant Physiologists, 2001)
The disaccharide trehalose has strong effects on plant metabolism and development. In Arabidopsis seedlings, growth on trehalose-containing medium leads to an inhibition of root elongation, an accumulation of starch in the shoots, an increased activity of ADP-Glc pyrophosphorylase (AGPase), and an induction of the expression of the AGPase gene, ApL3 (A. Wingler, T. Fritzius, A. Wiemken, T. Boller, R.A. Aeschbacher [2000] Plant Physiol 124: 105–114). We used Arabidopsis mutants deficient in starch synthesis to examine whether the primary effect of trehalose was to affect carbohydrate allocation by the induction of AGPase in the photosynthetic tissue. In a mutant lacking the large AGPase subunit, ApL1, (adg2-1 mutant) growth on trehalose restored AGPase activity and led to a strong accumulation of starch in the shoots. In contrast, starch synthesis could not be induced in a mutant lacking the small AGPase subunit, ApS, (adg1-1 mutant) or in a mutant lacking plastidic phosphoglucomutase (pgm1-1 mutant). These results indicate that ApL3 can substitute for ApL1 in the AGPase complex. In addition, root elongation in the mutants, especially in the adg1-1 mutant, was partially resistant to trehalose, suggesting that the induction of ApL3 expression and the resulting accumulation of starch in the shoots were partially responsible for the effects of trehalose on the growth of wild-type plants.